The flexible skew Laplace distribution. Issue 23 (1st December 2016) - Yilmaz, Abdullah
ABSTRACT: Skew-symmetric distributions have been discussed by several research-ers. In this article we construct a skew-symmetric Laplace distribution, which is the generalization of distribution given by Ali et al. (2009 ) and Nekoukhou and Alamatsaz (2012 ). This new distribution contains more parameters, and this induces flexibility properties, such as unimodality or bimodality. We study on some properties of this distribution. In the last section we also provide an application with a real data. Concerning example has recently been discussed by Nekoukhou et al. (2013 ) to apply to their model. We compare the behavior of our distribution to their distribution on this example.